Gerador Automático de Requisitos e Descrições de Casos de Teste - Roberto Ribeiro Lima (2018)
This document addresses a topic within the automotive industry, focusing on the electronic control units present in a modern automobile, known as ECUs. These ECUs are embedded systems responsable for controlling one or more automobile systems. The ECU configuration is described in an XML (* .arxml) file that follows a schema defined by AUTOSAR called ECU Extract. Typically, this file is generated by the OEM, i.e., by the respective automobile manufacturer. In this document we will present a solution related with RE, thus addressing the definition, documentation and maintenance of the requirements of software systems. The solution provides a list of requirements automatically from the ECU Extract together with the description of test cases for such requirements. A test case is a set of execution conditions and expected results to acheive a desired goal, such as includes a specific path in the program executes or checking whether the compilation includes a specific requirement. The requirements and tests case for an ECU Extract will be created automatically, replacing the manual process that is used currently. This way, the requirements engineering process can be made more effiction and resilient to human errors. We emphasize that the focus of our solution is not to execute the tests automatically, but instead, to provide documentation that is easy to undertand for the Test department that after will test and validate the ECU requirements automatically extracted from the ECU Extract, comparing for a set of scenarios, the values obtained with those expected. This Dissertation will begin by addressing the development of automotive control systems, explaining the basic concepts and frameworks that are involved. Then it will present the problem, the proposed solution and next the working methodologies used in the solution development. Finally, we present the solution architecture, the tests to validate the solution and final conclusions.